2015
DOI: 10.1111/1753-0407.12304
|View full text |Cite
|
Sign up to set email alerts
|

Intensive walking exercise for lower extremity peripheral arterial disease: A systematic review and meta‐analysis

Abstract: Background: Supervised treadmill exercise is the recommended therapy for peripheral arterial disease (PAD) patients with intermittent claudication (IC). However, most PAD patients do not exhibit typical symptoms of IC. The aim of the present study was to explore the efficacy and safety of intensive walking exercise in PAD patients with and without IC. Methods: The PubMed, Embase and Cochrane Library databases were systematically searched. Randomized controlled trials comparing the effects of intensive walking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 72 publications
2
36
0
1
Order By: Relevance
“…Because the field of exercise intervention in cardiovascular diseases is huge, we kept the title of this review is focused on peripheral arterial disease (PAD) only in human and animals to help in improving the transitional understanding between the animal and human. In PAD patients exhibiting intermittent claudication (IC), supervised and well-coordinated exercise is an instrumental medication ( 75 ). It is noteworthy, nonetheless, that the majority of PAD patients don't exhibit typical IC symptoms, and there is considerable disagreement in the literature surrounding the impact of exercise on PAD patients ( 19 ).…”
Section: Does Diabetes Attenuate the Benefits Of Exercise In Pad Patimentioning
confidence: 99%
“…Because the field of exercise intervention in cardiovascular diseases is huge, we kept the title of this review is focused on peripheral arterial disease (PAD) only in human and animals to help in improving the transitional understanding between the animal and human. In PAD patients exhibiting intermittent claudication (IC), supervised and well-coordinated exercise is an instrumental medication ( 75 ). It is noteworthy, nonetheless, that the majority of PAD patients don't exhibit typical IC symptoms, and there is considerable disagreement in the literature surrounding the impact of exercise on PAD patients ( 19 ).…”
Section: Does Diabetes Attenuate the Benefits Of Exercise In Pad Patimentioning
confidence: 99%
“…Supervised exercise programmes are known to give the most convincing benefits. [22][23][24][25][26][27][28] In fact, lifestyle modifications, particularly exercise (walking, intensive walking, and supervised exercise), are effective in increasing the ICD [18][19][20][21][22] : supervised exercise programmes can increase the ICD by 81.2-143.8 m, whereas free exercise shows inferior results. 23,24 According to the therapeutic algorithms currently in use, patients with IC start treatment with supervised exercised programmes; drugs are added in cases of insufficient improvement after three to six 3,7,9,10 months.…”
Section: Introductionmentioning
confidence: 99%
“…The literature centered on symptomatic populations has concluded that exercise programs are associated with improved maximum walking distance and time, pain-free walking distance, 6-minute walk, WIQ scores, and quality of life. 9,[12][13][14] Expecting unselected populations to achieve improvements in ambulation may not be reasonable if they are not reporting symptoms; however, if patients are unaware of symptoms because they have limited their activity levels, treatment could potentially improve ambulation and quality of life. Several observational studies of screen-detected or asymptomatic populations do show that those with a low ABI have statistically significant worse measures of function than those with a normal ABI, including 6-minute walk distance, 4-m walking velocity, 400-m walk time, SF-36 physical functioning subscale scores, and WIQ distance and speed scores.…”
Section: Discussionmentioning
confidence: 99%
“…8 All previously included studies were reviewed for potential inclusion, and Ovid MEDLINE, PubMed, and the Cochrane Central Register of Controlled Trials were searched to identify new literature published between January 2012 and May 2, 2017 (eMethods in the Supplement). Additionally, reference lists from recent systematic reviews [9][10][11][12][13][14][15][16][17] were examined and ClinicalTrials.gov was searched to identify relevant ongoing trials. Since May 2, 2017, ongoing surveillance through article alerts and targeted searches of journals with a high impact factor and journals relevant to the topic were conducted to identify major studies published in the interim that may affect the conclusions or understanding of the evidence and therefore the related USPSTF recommendation.…”
Section: Data Sources and Searchesmentioning
confidence: 99%